Візуалізація та обробка результатів технології Eye Tracking - Євсєєв, В. В.; Бортнікова, В. О.; Демська, А. І. (ХНУРЕ, 2019)
The paper describes the results of experimental studies of visualization and processing of results using Eye Tracking technology. Website research is based on image acquisition and processing. Pixelization algorithm is used to obtain the image. Image analysis consists of determining various quantitative image data (parameters). This solution will allow to substantiate the possibility of automating the process of designing the optimal location of the main graphic elements on the site, depending on its orientation and content.
Keywords: Eye Tracking; image analysis; processing of results